Massive scalar field perturbation on Kerr black holes in dynamical Chern–Simons gravity - Zhang, Shao-Jun (The European physical journal. C, Particles and fields, 2021)
We study massive scalar field perturbation on Kerr black holes in dynamical Chern–Simons gravity by performing a ( 2 + 1 ) -dimensional simulation. Object pictures of the wave dynamics in time domain are obtained. The tachyonic instability is found to always occur for any nonzero black hole spin and any scalar field mass as long as the coupling constant exceeds a critical value. The presence of the mass term suppresses or even quench the instability. The quantitative dependence of the onset of the tachyonic instability on the coupling constant, the scalar field mass and the black hole spin is given numerically.